2019
DOI: 10.1111/jphp.13182
|View full text |Cite
|
Sign up to set email alerts
|

The safety and tolerability of Annona muricata leaf extract: a systematic review

Abstract: Objectives Annona muricata, also known as graviola, soursop and guanabana, has been widely utilised for the treatment of a range of cancers. The mechanism of action and the efficacy of A. muricata and its constituents in the treatment of cancer have been comprehensively reviewed. The aim of this systematic review was to summarise the available literature that reports on factors related to the safety and tolerability of A. muricata leaf extract and its acetogenins. Methods In‐vitro, preclinical animal studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…In the hematological analysis done in this study, the effect of the fruit extract was also evaluated on the white blood cell (WBC) count. Like previous studies [55], the WBC count in this study demonstrated no significant difference compared to the control. This result may signify that that Annona muricata ethanolic fruit extract does not possess toxins suppressing the average production of WBC (leucopenia) or inducing leukocytosis.…”
Section: Alaninesupporting
confidence: 69%
“…In the hematological analysis done in this study, the effect of the fruit extract was also evaluated on the white blood cell (WBC) count. Like previous studies [55], the WBC count in this study demonstrated no significant difference compared to the control. This result may signify that that Annona muricata ethanolic fruit extract does not possess toxins suppressing the average production of WBC (leucopenia) or inducing leukocytosis.…”
Section: Alaninesupporting
confidence: 69%
“…Acetogenins have been identified as one of the major bioactive compounds of A. muricata with activity on several cancer cell lines [15,16]. The ethanol extracts obtained from aerial parts from A. muricata in combination with doxorubicin showed important cytotoxic activity on 4T1 cells and other cancer cell lines [15][16][17][18][19][20][21][22]. Although there is an extensive amount of information about the cytotoxic properties of A. muricata, no information is available regarding its anti-cancer potential in specifically breast cancer using the extracts of plants collected in different periods of the year, and regarding the location of the place of recollection and its influences on their pharmacological and toxic properties.…”
Section: Introductionmentioning
confidence: 99%
“…More than 400 compounds of acetogenins were described. This tropical plant grows in India, South and Central America, Indonesia and the Philippines [85][86][87]. Previously, graviola leaves were used in traditional folk medicine to treat several diseases, i.e., infections or inflammations, as well as insomnia, diabetes, headaches, arthritis, malaria or parasites [88,89].…”
Section: Acetogenins From Annona Muricatamentioning
confidence: 99%
“…Previously, graviola leaves were used in traditional folk medicine to treat several diseases, i.e., infections or inflammations, as well as insomnia, diabetes, headaches, arthritis, malaria or parasites [88,89]. Among the chemical compounds found in graviola extract, the anti-cancer agent seems to be acetogenin (Figure 1F) [85]. Graviola is usually presented in a leaf-powder form and can influence free radical production and the level of ROS by scavenging peroxy and nitrogen radicals [90].…”
Section: Acetogenins From Annona Muricatamentioning
confidence: 99%